Khotanese varga‑ ‘fruit (of an action)’: A Buddhist Term Borrowed from Bactrian - Schoubben, Niels ca. 20./21. Jh. (Indo-Iranian journal, 2025)
The present article has a twofold aim: (i) to present further evidence that (Late) Khotanese had a lexeme varga‑ ‘fruit (of an action)’, next to the homonymous varga‑ ‘group, mass, multitude’ (borrowed from Buddhist Sanskrit); and (ii) to argue that varga‑ ‘fruit (of an action)’ is not an inherited word but a loan from Bactrian *βαργο /vargə/ < *bara-ka‑, which is attested in Manichaean Bactrian as ꞵrg ‘fruit (of an action)’.